The Juvenile Criminal Justice System in Supporting Balikpapan's Efforts to Become a Child-Friendly City - Nooranam Assri Abdiaswari; Fajar Apriani; Cathas Cathas Teguh Prakoso (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This study explores the role of local government meta-governance in integrating child protection systems within the juvenile criminal justice framework to support Balikpapan’s efforts in becoming a Child-Friendly City. Using a qualitative descriptive-analytic method, the research examines the interaction among institutional actors, policy coordination, and restorative justice implementation through interviews, observations, and document analysis. The findings indicate that the effectiveness of the juvenile justice system depends on the strength of institutional synergy and the ability of local governments to act as orchestrators that align various sectors under shared principles of child protection. The study reveals that diversion and restorative justice mechanisms represent a transformative shift from punitive approaches toward rehabilitative and developmental justice, while meta-governance ensures sustainable coordination and accountability. The results emphasize that Balikpapan’s progress toward a Child-Friendly City is determined by the capacity of its governance structure to institutionalize restorative values, integrate multi-sector collaboration, and uphold children’s rights through inclusive and ethical policy practices.